2015
DOI: 10.1007/s12178-015-9280-0
|View full text |Cite
|
Sign up to set email alerts
|

A current review of core decompression in the treatment of osteonecrosis of the femoral head

Abstract: The review describes the following: (1) how traditional core decompression is performed, (2) adjunctive treatments, (3) multiple percutaneous drilling technique, and (4) the overall outcomes of these procedures. Core decompression has optimal outcomes when used in the earliest, precollapse disease stages. More recent studies have reported excellent outcomes with percutaneous drilling. Furthermore, adjunct treatment methods combining core decompression with growth factors, bone morphogenic proteins, stem cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 51 publications
1
71
0
3
Order By: Relevance
“…In recent years, non-surgical treatments for knee osteoarthritis have become more widely used, such as PRP, corticosteroid injection and hyaluronic acid (25,28). A previous study described various methods for knee osteoarthritis treatment, including decompression with bone morphogenic proteins, growth factors, bone grafting and stem cells (29). In addition, a systematic review and meta-analysis compared the efficacy of PRP and hyaluronic acid for treatment of knee osteoarthritis and it was demonstrated that PRP injection was more effective than hyaluronic acid in a 2-year meta-analysis (12).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, non-surgical treatments for knee osteoarthritis have become more widely used, such as PRP, corticosteroid injection and hyaluronic acid (25,28). A previous study described various methods for knee osteoarthritis treatment, including decompression with bone morphogenic proteins, growth factors, bone grafting and stem cells (29). In addition, a systematic review and meta-analysis compared the efficacy of PRP and hyaluronic acid for treatment of knee osteoarthritis and it was demonstrated that PRP injection was more effective than hyaluronic acid in a 2-year meta-analysis (12).…”
Section: Discussionmentioning
confidence: 99%
“…A current review of the literature on CD was published in 2015 by Pierce et al 19 The ideal lesion to be treated with CD is pre-collapse and small. Standard CD procedure is typically performed by the drilling and removal of an 8- to 10-mm cylindrical core from the necrotic lesion.…”
Section: Resultsmentioning
confidence: 99%
“…Pierce and colleagues showed how more recent studies on CD reported better results than older studies; this could be due to a surgical improvement and a better selection of patients. 19 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, platelets actively participate in healing processes by delivering a broad spectrum of growth factors (insulin like growth factor, transforming growth factor b-I, platelet derived growth factor, and many others) and other active molecules (e.g., arachidonic acid metabolites, cytokines, chemokines, ascorbic acid, extracellular matrix proteins, and nucleotides) to the injured site (26).…”
Section: Mechanism Of Action Of Platelet Rich Plasmamentioning
confidence: 99%